Performance of Bio-Inspired Ship Hull - Siti Nur Azizah, Amran (Universiti Malaysia Sarawak (UNIMAS), 2020)
The functional properties of shark denticles have caught the attention of our engineers and scientist today due to the hydrodynamic effects of its surface roughness of the skin. The skin of a fast swimming shark reveals riblet structures that helps to reduce skin friction drag of the shark making its movement to be more efficient and faster. This research focuses on modification made on marine vessels which presents the study of biomimetic shark skin (BSS) on surface structure which function is to enhance the hydrodynamic effect of the vessels. Model of simplified version shark skin on rectangular planes (RP), container ship (CS) models and speedboat models are both constructed using Solidworks and computational fluid dynamic (CFD) simulations are then carried out to predict the effectiveness of the hydrodynamic effects of the biomimetic shark skins on both models. Experimental study on speedboat models has also been carried out in order to validate the numerical result obtained. The results are then, compared with both plain models and models with BSS. The presence of BSS on rectangular planes provides significant improvement up to 15% reduction in shear stress and about 25% improvement in velocity flow along the rectangular plane with BSS. Similar to rectangular plane models, improvements for both velocity and shear stresses can also be found in container ship models with BSS. While for both numerical and experimental study of speedboat models, it is also discovered that the implementation of BSS gives positive outcomes in drag reduction. Further discussion on other parameters for the speedboat models like wave height, divergence wave and drag coefficient are also demonstrated in this thesis.